TEACHING RECOUNT WRITING BY USING TAD (TRANSITION ACTION DETAILS) STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMPN 16 PALEMBANG - indah purwati (Edukasi, 2017)
The objectives of the study are: 1) to find out whether or not there is a significant improvement on the eighth grade students’ recount writing achievement who are taught by using TAD Strategy at SMPN 16 Palembang, and 2) to find out whether or not there is a significant difference between the eighth grade students’ recount writing achievement between those who are taught by using TAD Strategy and those who are not at SMPN 16 Palembang. The population of the study was the eighth grade students of SMPN 16 Palembang in the academic year of 2016/2017. The sample of the study was taken by using nonrandom sampling method. The writer selected class VIII.4 as the control group and VIII.2 as the experimental group. It consisted of 50 students, 25 students for control group and 25 students for experimental group. In this study, the writer used quasi experimental design. The test was used as pretest and posttest for both groups. The result showed that teaching recount writing by using TAD (Transition Action Details) Strategy had a significant effect on the students’ writing achievement. It can be seen from the result of the posttest of each group. The achievement of the experimental group was higher than control group. Based on the independent sample t-test analysis, it was found that t-obtained was higher than t-table. The t-obtained was 5.013 and t-table was 2.0639 at the significance level p < 0.05 in two tailed testing with the degree of freedom. It means that there was significant difference in writing achievement between the students who were taught by using TAD than those who were taught by using teacher’s method. From the result of the test, it implies that TAD strategy could be used as an alternative strategy in teaching writing. In addition, the students’ writing problems can be minimized by applying the TAD strategy. The TAD strategy created the situation that was more enjoyable than before. It made the students enthusiastic to do the tasks because the column attracted their attention. Those reasons made the students easier to improve their writing skill.